Quantifying curing and composition effects on compressive and tensile strength of 160–250 MPa RPC. (30th April 2020) - Rong, Qin; Hou, Xiaomeng; Ge, Chao
Highlights: An RPC with high compressive strength of 250 MPa was developed. Curing effects on RPC160-250 are quantified. Compared with RPC160, the increase of tensile strength of RPC250 was about 10%. Fire-induced spalling of RPC can be prevented by reducing water content to 0.4%. RPC250 can outperform steel in special applications due to higher strength to weight ratio. Abstract: Reactive powder concrete (RPC) with a compressive strength of 250 MPa was developed using ordinary raw materials without autoclaved pressure curing. Base on optimizing 35 mix proportions and curing conditions, a calculation formula for 160–250 MPa compressive strength RPC is proposed. Results showed that replacing quartz sand with river sand reduced RPC cost by 10%, while reducing compressive strength by 9–12%. Adding quartz powder (0.37 cement weight) increased compressive strength by 2–4% but reduced fluidity. The influence of curing time, heating time, and temperature on RPC compressive strength was quantified. The recommended steel fiber content is 2–3% to achieve a high compressive strength. Curing RPC in 90 °C steam for 3d and heating to 300 °C for 24 h, increased RPC compressive strength to 250 MPa, an increase of 54% compared to curing with 90 °C steam for 3d only. This is primarily due to ''internal autoclave" occurring in RPC at high temperature. Compared with steam curing, after 200–300 °C heat, the increase in RPC split-tensile strength and flexural tensile strength was approximately 10%. After 200–300 °C heat, fire-induced spalling in RPC can be prevented because the water content was reduced to 0.4%. RPC can be applied in indoor structures without fire insulation. RPC250 exhibits higher strength to weight ratio and could outperform steel in certain applications.